The impact of public investment on private investment in Mexico, 1980-2007 - Fonseca Hernández, Felipe de Jesús (Estudios Económicos de El Colegio de México, 2009)
Even though there is a growing consensus in the existing literature on the positive effect that public investment generates for economic growth, its impact on private investment is by no means a settled issue. This study seeks to determine empirically the relation between these two variables for the Mexican economy during the 1980-2007 period. The results of dynamic estimations yield a partial crowding out of public investment in the short run, while, in the long run, it exerts a weak and marginal complementarity effect on private investment.